Beginning community engagement at a busy biomedical research programme: Experiences from the KEMRI CGMRC-Wellcome Trust Research Programme, Kilifi, Kenya - Marsh, V; Kamuya, D; Rowa, Y; Gikonyo, C; Molyneux, S (2008)
There is wide acknowledgement of the need for community engagement in biomedical research, particularly in international settings. Recent debates have described theoretical approaches to identifying situations where this is most critical and potential mechanisms to achieve it. However, there is relatively little published experience of community engagement in practice. A major component of the Kenya Medical Research Institute (KEMRI) Wellcome Trust Research Programme is centred on Kilifi District General Hospital and surrounding community of 240,000 local residents. Documented community perceptions of the research centre are generally positive, but many indicate a low understanding of research and therapeutic misconceptions of its activities. As in other settings, these misunderstandings have contributed to concerns and rumours, and potentially undermine ethical aspects of research and local trust in the institution. Through a series of consultative activities, a community engagement strategy has been developed in Kilifi to strengthen mutual understanding between community members and the Centre. One important component is the establishment of a representative local resident network in different geographic locations commonly involved in research, to supplement existing communication channels. Early implementation of the strategy has provided new and diverse opportunities for dialogue, interaction and partnership building. Through the complex social interactions inherent in the community engagement strategy, the centre aims to build context specific ethical relations with local residents and to strengthen understanding of how ethical principles can be applied in practice. Evaluations over time will assess the effectiveness and sustainability of these strategies, provide generalisable information for similar research settings, and contribute to debates on the universality of ethical principles for research. This paper aims to summarise the rationale for community engagement in research, drawing on published literature and local findings, to outline the process of community engagement in Kilifi and to describe issues emerging from its development and early implementation. © 2008 Elsevier Ltd. All rights reserved.